Innovation, incubation and entrepreneurship : case studies from IIT Kanpur - Phani, B. V.; Khandekar, Sameer (IITK directions ;, 2017)
This book focuses on promoting entrepreneurial ecosystems within universities and educational institutes. It especially emphasizes the thriving systems and practices existing within the Indian Institute of Technology Kanpur (IITK). It discusses cases and successes of the SIDBI Incubation and Innovation Centre in the Institute. This edited volume highlights the vision of IITK and describes a few of the major achievements of the past few years. It especially showcases the requirements and challenges of creating, sustaining, and boosting such entrepreneurial ecosystems and incubation centres. The contents of this book will be useful to researchers, administrators, and corporate collaborators working in the area of monetizing technology coming from educational institutions by converting it to successful products and business ideas.